Optimal Taxation of Human Capital and Credit Constraints - Bas Jacobs (Tinbergen Institute, 2002)
We study optimal linear income taxation in a model with heterogeneous agents where earnings potentials are endogenously determined through human capital accumulation. Agents differ in initial conditions and ability to learn. Capital market imperfections prevent poor agents to invest optimally in human capital. We show that optimal linear tax rates on human capital are positive, even in absence of redistributive preferences of the government. A more progressive tax system has efficiency gains because credit constraints are relaxed. Numerical calculations show that optimal linear tax rates are significantly increased when capital market imperfections are present.
Keywords: H21; H23; J24; 330; optimal linear taxation; human capital; credit constraints; Einkommensteuer; Steuertarif; Optimale Besteuerung; Bildungsinvestition; Bildungsfinanzierung; Liquiditätsbeschränkung; Theorie